Molecular Mechanisms of Synaptic Plasticity 2.0: Dynamic Changes in Neurons Functions,Physiological and Pathological Process - Martella, Giuseppina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is a continuation of our previous Special Issue "Molecular Mechanisms of Synaptic Plasticity: Dynamic Changes in Neurons Functions". With the aim to present good research papers provided by specialists, this Special Issue published basic research and pre-clinical research articles, case reports, case series or clinical image articles, short communications, and review articles.